Factors influencing the level of self-stigmatisation in people with mental illness. (June 2018) - Kalisova, Lucie; Michalec, Jiri; Hadjipapanicolaou, Demetra; Raboch, Jiri
Aim: The aim of this study was to assess sociodemographic factors and factors connected with treatment of mental illness and to decide whether they can influence the level of self-stigma. Method: Sociodemographic characteristics (age, gender, family status, level of employment, level of education) and characteristics related to illness and treatment (diagnosis, length of treatment, adherence to treatment) were gathered in a group of patients in stable mental condition, without acute symptoms of mental illness. Self-stigma was measured using the Self-stigma of Mental Illness Scale – short form (SSMIS-SF). Results: The sample included 197 patients: 99 patients in group 1 (G1) with psychosis and 98 in group 2 (G2) with anxious and affective disorders. The average age was 44.15 ± 12.91 years, the length of illness was 11.67 ± 9.21 years and 48% of patients were men. The total average SSMIS-SF score was 61.54 ± 23.34. We found no statistically significant difference in the total level of self-stigmatisation between these groups ( t (197) = 0.77; p = .441). The level of self-stigmatisation (total score of SSMIS-SF) in patients in G1 (psychosis) increased with the length of illness r (99) = .253; p = .011. Employment status seems to correlate with the level of self-stigmatisation ( F (3, 184) = 5.27; p = .002). Patients unemployed and on disability pension had higher levels of self-stigmatisation than patients working full-time. Patients who took medication regularly (full medical adherence) had lower scores of SSMIS-SF total scores in comparison with patients with lower compliance ( t (195) = 3.476; p = .001; Cohen's d = .25). Conclusion: According to our results, with regard to the factors that were followed, self-stigmatisation correlates with the presence of employment (social inclusion), duration of illness in patients with psychosis and treatment adherence. We did not find a statistically significant influence of age, gender, marital status or clinical diagnosis on the level of self-stigma.